Quantifying the impact of the predator guild on California red scale in Spanish citrus - Bouvet, Juan Pedro; Urbaneja, Alberto; Pérez-Hedo, Meritxell; Monzó, César (Consejo Superior de Investigaciones Científicas (CSIC), 2024)
Póster